Multimodal approach in the pre‐surgical evaluation of focal epilepsy surgery candidates: how far are we from a non‐invasive ESI‐based "sourcectomy"?. Issue 4 (17th August 2021) - Nobile, Giulia; Consales, Alessandro; Tortora, Domenico; Pacetti, Mattia; Gianno, Francesca; Arnaldi, Dario; Morbelli, Silvia; Mancardi, Margherita; Sartori, Ivana; Cossu, Massimo; Nobili, Lino; Cataldi, Matteo
Abstract: The management of drug‐resistant patients with focal epilepsy is often challenging. Surgery is recognised as a useful and effective treatment option. The identification of the epileptogenic zone relies on the integration of clinical, neurophysiological, and neuroimaging findings. The role of non‐invasive functional neuroimaging techniques has been reported to add diagnostic accuracy to first‐line evaluations, avoiding invasive presurgical examinations in selected cases. In this view, we report the case of a 16‐year‐old male suffering from drug‐resistant focal epilepsy with episodes rarely evolving to a bilateral tonic‐clonic seizure. Conventional 1.5T and 3T MRI were considered uninformative. Based on electro‐clinical data, focal cortical dysplasia was suspected. The epileptogenic zone was identified with the integration of further non‐invasive functional neuroimaging techniques ([18F]‐fluorodeoxyglucose positron emission tomography and arterial spin labelling), where electrical source imaging played the main role. All techniques pointed towards a cortical region, where a 7T brain MRI identified a signal alteration consistent with focal cortical dysplasia. A tailored resection of the lesion located in the inferior frontal sulcus was performed, guided by intraoperative electrocorticography (strip and depth electrodes). Postoperative seizure freedom was achieved. The histopathology confirmed the suspicion of focal cortical dysplasia type IIa. With this case report, we highlight the importance of a multimodal approach in the presurgical evaluation of candidates for epilepsy surgery, which, in selected cases, may allow invasive procedures, such as stereo‐EEG, to be avoided in the investigation of the epileptogenic zone. Moreover, we underline the pivotal role of EEG source imaging, especially when focal cortical dysplasia is suspected.